The Use Of Portrayals For Assessing Nursing Students’ Oral Skill - Didi Hermawan (Universitas Majalengka, 2021)
Sequence of pictures, maps and diagrams can be used to assess speaking. We can use pictures for testing the production of significant phoneme contrast, while a portrayal of a scene or an incident can be used for examining the total oral skills. This article is a descriptive study that the data is collcted from seconder data which is obtained by library reference. The discussion focuses on the use of portrayals for description, narration and procedure. The aim of this paper is to figure out the use of portrayals for assessing students’ oral skill in Poltekkes Kemenkes Semarang Prodi Tegal. Based on the elaboration, portrayals enable the students to explore their imagination, particularly portrayals of a nurse or a doctor handling patient or something around hospital. These erase the obstacles of the tester in assessing the nursing students’ oral skills. The students’ knowledge such as the vocabularies and the expressions related to Asuhan Keperawatan or called a sequence step caring patient come out when assessment. Furthermore, the tester is able to capture score based on their performance